Sir John Macpherson, the first but sometimes overlooked Professor of Psychiatry at the University of Sydney. (August 2014) - White, Richard T
Objective: To chronicle the creation of the Chair of Psychiatry at the University of Sydney, and the career and legacy, in New South Wales, of the first incumbent, Professor Sir John Macpherson CB MD FRCPE. Conclusions: The creation of the Chair, Macpherson's appointment, and his contributions to psychiatry in Sydney during the 52 months of his tenure, are well documented in contemporaneous sources and demonstrate that he was a very worthy Foundation Professor of Psychiatry at the University of Sydney. There are several possible reasons why Macpherson has been overlooked, including an erroneous statement in The World History of Psychiatry (1975) that William Siegfried Dawson, his successor from 1927 to 1952, was the first Professor of Psychiatry.